Serum glutathione transferase does not respond to indole-3-carbinol: A pilot study - Daniel R McGrath; Hamid Frydoonfar; Joshua J Hunt; et al (Dove Medical Press, 2010)
Daniel R McGrath1, Hamid Frydoonfar2, Joshua J Hunt3, Chris J Dunkley3, Allan D Spigelman41Ipswich Hospital, Ipswich, UK; 2Hunter Pathology Service, New South Wales; 3Royal Newcastle Centre, Newcastle; 4St Vincent’s Clinical School, Sydney, AustraliaBackground: Despite the well recognized protective effect of cruciferous vegetables against various cancers, including human colorectal cancers, little is known about how this effect is conferred. It is thought that some phytochemicals found only in these vegetables confer the protection. These compounds include the glucosinolates, of which indole-3-carbinol is one. They are known to induce carcinogen-metabolizing (phase II) enzymes, including the glutathione S-transferase (GST) family. Other effects in humans are not well documented. We wished to assess the effect of indole-3-carbinol on GST enzymes.Methods: We carried out a placebo-controlled human volunteer study. All patients were given 400 mg daily of indole-3-carbinol for three months, followed by placebo. Serum samples were tested for the GSTM1 genotype by polymerase chain reaction. Serum GST levels were assessed using enzyme-linked immunosorbent assay and Western Blot methodologies.Results: Forty-nine volunteers completed the study. GSTM1 genotypes were obtained for all but two volunteers. A slightly greater proportion of volunteers were GSTM1-positive, in keeping with the general population. GST was detected in all patients. Total GST level was not affected by indole-3-carbinol dosing compared with placebo. Although not statistically significant, the GSTM1 genotype affected the serum GST level response to indole-3-carbinol.Conclusion: Indole-3-carbinol does not alter total serum GST levels during prolonged dosing.Keywords: pilot study, colorectal cancer, glutathione transferase, human, indole-3-carbinol